The relationship of the Arabic language in the achievement of other academic subjects among students (Journal of the College of Basic Education, 2022)
The aim of the current research is to know the relationship of the Arabic language in the achievement of other subjects for third-grade intermediate students, and to achieve this goal; The researcher imposed zero hypotheses regarding the impact of the Arabic language on the achievement of other academic subjects, and there were (8) hypotheses. Male and female students, and after applying the research variables to the sample students and analyzing the results statistically, it appeared that there is an effect (of Islamic education, mathematics and social sciences) in the Arabic language, and in light of the research results, the researcher concluded, that there are correlations between the Arabic language and the subject of Islamic education and mathematics and the subject of social sciences. The other subjects had an impact on the Arabic language for the third intermediate grade students, and in light of the research results and conclusions, the researcher recommends the following: That the Ministry of Education prepare enrichment activities to develop the Arabic language for the third intermediate grade. And if the Ministry of Education instructs, through its curricula, to develop the Arabic language in a manner that is appropriate for each stage of study, and to develop and complement the current research, the researcher suggests conducting a study on the relationship of literature with other branches of the Arabic language. Or a study on the relationship of the Arabic language in the achievement of academic subjects for students of other academic levels.